2020
DOI: 10.1111/jvim.15811
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a 3‐dimensional ultrasound device for noninvasive measurement of urinary bladder volume in dogs

Abstract: Background The BladderScan Prime Plus (BPP; Verathon, Bothell, Washington) is an application‐specific, three‐dimensional ultrasound device used for human, point‐of‐care volumetry of the urinary bladder. Objective To estimate the BPP's accuracy, repeatability, and optimized settings for assessing urinary bladder volumes in dogs, a variable utilized in assessing micturition disorders. Animals Twenty‐four, client‐owned, healthy, male dogs presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…A previous study in dogs found that the accuracy of 3D ultrasound varied between the size of dogs and device setting utilized. 23 However, in our study we used a newer model of the Verathon BladderScan Prime Plus which automatically adapts to patient size and no longer has separate adult and child settings. Additional studies are warranted to investigate the accuracy of the 3D ultrasound device in different sizes of dogs and to determine if it is clinically useful in cats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study in dogs found that the accuracy of 3D ultrasound varied between the size of dogs and device setting utilized. 23 However, in our study we used a newer model of the Verathon BladderScan Prime Plus which automatically adapts to patient size and no longer has separate adult and child settings. Additional studies are warranted to investigate the accuracy of the 3D ultrasound device in different sizes of dogs and to determine if it is clinically useful in cats.…”
Section: Discussionmentioning
confidence: 99%
“…The previous study in dogs reported that an experienced operator determined a significantly higher mean volume than did novice. 23 Therefore, we believe more extensive formal training of clinical staff might result in more accurate bladder measurements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inclusion criteria included hospitalization in any of the above areas for a minimum of 24 hours, ability to walk and urinate without assistance, no behavioral aggression, and no reported lower urinary tract disorders that might affect their ability to naturally void. Enrolled dogs had to weigh ≥5 kg based on increased accuracy of the device to capture bladder tracings in dogs above this weight 19,20 . Dogs were excluded if they had suspected oliguric or anuric renal failure, any history of a neurologic disorder, because of the known impact of these disorders on urine production or bladder function, or if they received an epidural during their hospitalization.…”
Section: Methodsmentioning
confidence: 99%
“…The 3D ultrasound device is intended to be used by operators with varying levels of expertise, allows for quick “bedside” measurements, and limits examination time because it reports an estimated volume in real time. Clinical application of 3D ultrasound in veterinary medicine is validated in dogs, and accurate in determining UBV and comparable to the gold standard 2D ultrasound method 19,20 . Detection of an increased URV and frequent monitoring in hospitalized dogs could be useful in identifying early signs of urinary retention.…”
Section: Introductionmentioning
confidence: 96%